Transforming Education Through Blockchain: A Systematic Review of Applications, Projects, and Challenges - Xianxian Wang; Muhammad Younas; Yicun Jiang; Muhammad Imran; Norah Almusharraf (IEEE Access)
Blockchain technology has revolutionized several fields, including finance, healthcare, and supply chain management. The unique features of blockchain, notably decentralization, trustworthiness, and security, have attracted considerable attention from researchers investigating its application in education. Within the education sphere, blockchain applications protect academic records, ensure their trustworthiness, reduce fraud, and improve the value of educational assets. Blockchain projects in education play a crucial role in establishing a more dependable and transparent system for verifying academic credentials and achievements, benefiting students and institutions alike. Many previous studies have provided limited insight into the practical implementation of blockchain technology’s role in education. This systematic study follows Okoli and Schabram guidelines to analyze the 64 articles published between 2016 and 2023. This review encompasses the latest blockchain applications, projects, benefits, and adoption challenges in education. In this study, four main themes are discussed: 1) what are the potential applications of blockchain in education 2) What Blockchain projects are currently implemented in education 3) What benefits does blockchain offer to the education sector 4) What challenges are associated with the adoption of blockchain in education. Each theme includes a detailed discussion and prospective evidence-based findings in this study. This study draws the researcher’s attention to leveraging blockchain technology in future research and encourages educational institutions to develop blockchain applications, transforming from traditional systems to digital platforms. This study also identifies future research directions and acknowledges limitations.